The Relationship between the Degree of Stressors and the Coping Strategies of Older Adult Living in Nursing Home - Daning Widi Istianti (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2022)
Introduction: Stress is potentially overwhelming, especially for older adults. Different types of stressors require different coping strategies. This study aimed to find the relationship between the stressors and the coping strategies among the older adults at a nursing home in Yogyakarta, and to develop a stress debriefing program.Methods: This study utilized a quantitative research method with a descriptive correlational-comparative design. To develop the stress debriefing program, the questionnaires about stressors and coping strategies were used as the research instruments. The respondents recruited using purposive sampling with total of 100 older adults. Simple descriptive through to complex analyses and multivariate regression were carried out using SPSS.Results: The results showed that the p-value of the difference between the demographics and the degree of stressors was 0.70; while the p-value of the relationship between the degree of stressors and coping strategies was 0.07. It means that there was no significant relationship between the degree of stressors and the coping strategies of older adults living in nursing home.Conclusions: The results found that there was no significant relationship between the degree of stressors and the coping strategies employed by the respondents. Nurses should be aware of  the stressors and help the residents to develop  appropriate coping strategies.